STUDY OF PAN FIBER AND IRON ORE ADSORBENTS FOR ARSENIC REMOVAL - Bhatti, Zulfiqar Ali; Qureshi, Khadija; Maitlo, Ghulamullah; Ahmed, Shoaib (Salehan Institute of Higher Education, 2020)
The main idea to conduct this study is the treatment of hazardous arsenite (As+3) and arsenate (As+5)from water by two efficient adsorbetns i.e. polyacrylonitrile fiber (organic) and iron ore (inorganic). Polyacrylonitrile (PAN) fibers were chemically modified prior to loading iron using a solution of diethylenetriamine and aluminum chloride hexahydrate. The characterization of PAN fibers was performed through FTIR spectroscopy, which shows the binding of functional groups on PAN fibers surfaces. Atomic absorption spectrometer (AAS) was used to analyze arsenic concentration in samples. The impact of pH, dosage, shaking (contact) time and shaking speed was studied and parameters were optimized for further study. The highest adsorption of 98% is exhibited by modified PAN fiber for As+5 while for As+3 removal is 80%. Modified PAN also showed higher adsorption capacity of 42×103?g/g for As+5 which is better than the As+3 adsorption capacity 33×103 ?g/g. Overall results demonstrated that MPAN adsorbent is better than the iron ore adsorbent for the treatment of both As+3 and As+5. Comparative studies of PAN Fiber and iron ore adsorbents revealed that PAN fibers had better adsorption properties than iron ore for As+3 and As+5 in terms of percentage removal and capacity.